Men shen bao bei - Lai, Xiaozhen (Wen xue guan, 2017)
Keeping gates and doors guarded by supernatural gatekeepers is a thousand year old tradition. The two Tang Dynasty generals Wei Shichong and Qin Shubao travel to heaven and back to earth, experiencing five exciting adventures.